The Benefits of Using English Songs as A Medium For Learning English Vocabulary In Elementary School: A Documentary Study - Tanjung, Nadila; Nasution, Tuti Alawiyah Ramadani; Widyana, Airen; Sarahseti, Dian Fanny; Dalimunthe, Herika; Utama, Loudya Putri; Khodijah, Raifa Naswa; Hasibuan, Shafira Hasan; Pebrianti, Irpi Octia; Fadhilah, Raudhotul; Siregar, Deasy Yunita (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Using English songs as a medium for vocabulary learning has become an interesting and effective approach, especially at the primary school level. This article aims to explore the benefits of using songs as a medium in English vocabulary learning, focusing on increasing students' motivation and ease of remembering new vocabulary. The research method used is a documentary study that reviews related literature and previous research results on this topic. The results show that songs can increase students' learning motivation through fun elements and memorable rhythms. Songs also provide a natural context for vocabulary use, which helps students understand and remember words better. The use of English songs as a medium for vocabulary learning in primary schools is proven effective and is recommended to improve the quality of English learning, by paying attention to the selection of appropriate songs and appropriate teaching strategies. Further research is recommended to develop more structured and effective music-based learning strategies in Indonesia's primary education context.